Iraqi Secondary Schools Biology Teachers’ Competency And Performance In Laboratory Skills - Alsharifi, Estabraq Kadhim Abbas (2014)

(untitled)
The emphasis on laboratory skills for biology teachers has increased in recent years. Past researchers had mainly focused on the need for teachers to improve methods of inquiry and thinking skills to be similar to those of active scientists. Therefore, the purpose of this study is to identify biology teachers' competency and their performance as well as investigating the relationship between teachers' competency and performance in biology laboratory skills in secondary schools. Penekanan kepada kemahiran makmal bagi guru biologi telah meningkat pada kebelakangan ini. Pengkaji terdahulu rata-rata memberi tumpuan kepada keperluan guru untuk meningkatkan kaedah inkuiri dan kemahiran berfikir untuk mempunyai kemahiran seperti seorang saintis. Tujuan kajian ini adalah untuk mengenal pasti kompetensi guru biologi dan prestasi kemahiran mereka dalam makmal biologi (laboratory skills).